Developing a motivation-conscious second language teaching approach: a literature survey (BRAC University Journal, 2026)
Motivation is probably used as the most important factor when describing success and failure in second language (L2) learning. During the lengthy and often tedious process of mastering an L2, learners with sufficient motivation are expected to achieve success. One of the most important determinant factors of L2 learners’ motivation is teachers. Therefore, teachers’ use of motivational strategies is reasonably considered central in effective English language teaching. But, because of the large number of such strategies available in the existing literature, it is quite challenging for teachers to decide which one to implement in their own classrooms while giving due attention to all the other important aspects of their teaching and classroom management. Keeping this in mind, this literature review presents a detailed framework of practical motivational techniques for language teachers from which they can carefully choose the appropriate strategies that suit both learners and their contexts. And, to begin with, a smaller set of ten motivational core-strategies has also been offered for Bangladeshi English language teachers that can readily be used in Bangladeshi context when trying to implement a motivation-conscious teaching approach.